ПСИХОЛОГІЧНІ ОСОБЛИВОСТІ ОСІБ, СХИЛЬНИХ ДО УНИКАННЯ В СКЛАДНИХ ЖИТТЄВИХ СИТУАЦІЯХ (World Science, 2020)
A comparison and analysis of temperament peculiarities and character features, self-regulation, cognitive and activity style, communicative, perceptive and іnteractive competence, emotional intelligence and barriers in communication, emotional states and direction, life values, coping strategies for persons with different level of inclination to avoidance in complex life situations are made. Interconnections between inclination to avoidance and rigidity, reactivity, assertiveness, social contacting in complex life situations, asocial inclination, moral normativity, activity modeling and evaluation, chaotic and controlled cognitive and activity style, self-regulation, communicative competence, social intuition, conflict behavior, stress-resilience, aggressiveness, sadness, gnostic and gloristic emotional direction are analyzed and interpreted.